Multilingualism in Secondary Students: Its Effect on English Language Development in EFL Contexts - amanda, vivi (JURNAL MASYARAKAT NEGERI ROKANIA, 2025)
Abstract : This study investigates the role of multilingualism in supporting English language development among secondary students in an EFL context by employing a mixed-methods design integrating questionnaires and semi-structured interviews. The findings reveal that multilingual practices are widely used and positively perceived by learners, with questionnaire results showing high mean scores for the use of first and local languages to support comprehension, vocabulary learning, and classroom communication. Students reported greater confidence, reduced anxiety, and stronger motivation when multilingual strategies were incorporated into instruction. Interview data further demonstrated that students rely on their multilingual repertoires to make sense of complex English input, express ideas more freely, and actively participate in class discussions. Although some instances of language interference were identified, these occurrences also reflected developing metalinguistic awareness and opportunities for corrective learning. The discussion aligns these results with recent studies from the last seven years, reinforcing the view that translanguaging serves as a cognitive scaffold and affective support mechanism that enhances linguistic processing, identity affirmation, and communicative competence. The study contributes empirical evidence from the Indonesian EFL context, highlighting that structured and purposeful multilingual pedagogy can maximize students’ engagement and linguistic outcomes. The findings suggest that multilingualism should be recognized as a valuable instructional resource rather than a barrier, and teachers are encouraged to adopt guided translanguaging strategies to strengthen comprehension, motivation, and language accuracy.